Cultivation of Didacticism in the Arabic Literary Tradition of Nigerian Provenance - Mikail Adebisi Folorunsho (Indonesian Journal of Arabic Studies, 2022)
The Arabic literati of Nigerian provenance have made significant contributions to literary activities in the country. Thematically, the Arabic verses of the literati are compossed for divergent purposes. A perusal of the genres of these verses shows didacticism as the most cultivated theme. The paper examined the literary compositions amongst the Arabic literati with attention paid to their didactic writings, using one of them, Sheikh Mustafa JumuÊ»ah Adewale as a model. The paper revealed the propensity of the Nigerian Arabic poets for the cultivation of didacticism with their works on religious teachings, historical exposition, and morality and language studies. Their didactic contributions are predominantly in verses.Â  The study employed both historical and contextual methods, in assessing the intellectual background of the composer and the social and cultural contexts that spurred the development of the cultivation of this genre by the Arabic poets in Nigeria. Purposive sampling technique was employed in selecting â€™Al-HiwÄr, as specimen of their didactic verses. Content analysis method was employyed in examining the theme of the poem, with attention paid to the significance of the educational issues it captured. To achieve this, the original text of the QasÄ«dah was translated to English with concise thematic analysis. Apart from being a compass to researchers in Nigerian literary scholarship, the study provides information about the creativity of Nigerian Arabic literati, especially the verse-makers. Information obtained from the work could be a veritable tool in the efforts to unravel the significance of the literary contributions of the Arabic scholars to literary development in Nigeria.